On the number of negative eigenvalues of a Schrodinger operator with δ interactions - Ogurisu, O. (Methods of Functional Analysis and Topology, 2010)
We give necessary and sufficient conditions for a one-dimensional Schrodinger operator to have the number of negative eigenvalues equal to the number of negative intensities in the case of δ interactions.